Copolymer, treatment agent, and its manufacturing method and application
By developing a new copolyamide without fluorine, a treatment agent that can protect water and oil on food packaging paper was prepared, which solved the problem that existing packaging papers were difficult to protect water and oil at the same time, and achieved environmentally friendly and efficient packaging performance.
Patent Information
- Application Number
- JP2024553848
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-10
- Filing Date
- 2023-03-08
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing food packaging papers are difficult to have both water and oil protection, and traditional fluoride treatment methods have environmental pollution and health risks, so alternatives need to be found.
A new copolyamide without fluorine was developed. Through the good compatibility and surfactivity of the copolyamide with water, a treatment agent that can achieve water and oil protection on paper was prepared.
The treatment agent can effectively achieve water and oil protection on food packaging paper, and avoid environmental pollution and health risks due to its non-fluorine element.
Smart Images

Figure 2025509434000001 
Figure 2025509434000002 
Figure 2025509434000003
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to the following two Chinese patent applications: A Chinese patent application filed on March 10, 2022, with application number 202210233638.4 and the invention title "Copolymer, Paper Treatment Agent, and Paper Product"; and A Chinese patent application filed on March 10, 2022, with application number 202210233817.8 and titled "Water-dispersible polymer, composition containing the polymer, and application thereof." The above two patent applications are hereby incorporated in their entirety into this application. [Technical field]
[0002] The present invention relates to a copolymer, a treating agent, and a method for producing the same and applications thereof. [Background technology]
[0003] Currently, food packaging paper (paper, paper boxes, and paper tableware) is widely used as an environmentally friendly packaging material. Since food contains water and oils at the same time, food packaging paper should have both water and oil repellency to prevent damage and soiling of the user during use. Currently, there are two treatment methods to make paper water and oil repellent. One is to treat paper using a paper-plastic compound or film coating method to form a barrier layer on the surface of the paper to prevent the penetration of water and oil, but paper produced by this method cannot be recovered and reused, so it is not considered an environmentally friendly packaging method.
[0004] Another method is to use fluoride treatment, which can provide very good water and oil repellency to the paper due to the low surface tension of the fluoride itself. This method has traditionally been considered as an environmentally friendly solution for packaging paper, and products based on fluorochemical industry have been used to meet the market needs.
[0005] CN1149326A describes the preparation of a paper water- and oil-repellent treatment agent by compounding fluorinated polyurethane and acrylic acid ester. CN1222166A describes the preparation of a water- and oil-repellent treatment agent by using a fluorinated acrylic acid ester polymer. CN102575435B, CN101517018B describe the preparation of a water- and oil-repellent treatment agent by using different fluorinated acrylic acid ester polymers. CN100408649C, CN100351339C describe the preparation of a water- and oil-repellent treatment agent by using different fluorinated acrylic acid ester polymers. CN1304690C describes the preparation of a water- and oil-repellent treatment agent by using a polyene-based polyamine fluoride.
[0006] In recent years, the international community has become increasingly concerned about polyfluoroalkyl substances (PFAS). As PFAS are considered to be highly stable and difficult to decompose, the U.S. Environmental Protection Agency (EPA) has published a related report, preliminary risk assessment of the development toxicity associated with exposure to perfluorooctanoic acid and its salts (http: / / www.epa.gov / opptintr / pfoa / pfoara.pdf), which raised concerns about the environmental burden associated with PFAS substances. At the same time, the U.S. Environmental Protection Agency announced that fluorotelomers may generate PFAS through decomposition or metabolism, but this was not reported in the Federal Register (FR Vol68, No. 73 / April 16,2003[FRL-2303-8], http: / / www.epa.gov / opptintr / pfoa / pfoar.pdf). EPA Environmental News For Release: Monday April 14, 2003EPA intensifies scientific investigation of a chemical processing aid (http: / / www.epa.gov / opptintr / pfoa / pfoafacts.pdf), and related telomer products are widely used in textile finishing, paper, leather, fire protection foam and care products.
[0007] Fluorinated paper treatment agents are thought to be one of the sources of PFAS. The U.S. Food and Drug Administration (FDA) has also published related research https: / / www.fda.gov / food / chemical-contaminants-food / and-polyfluoroalkyl-substances-pfas, and companies that produce and supply fluorinated paper treatment agents have declared that they will remove fluorinated products from the paper treatment market in 2023. https: / / www.fda.gov / food / chemical-contaminants-food / authorized-uses-pfas-food-contact-applications
[0008] In light of the above situation, the food packaging industry is in need of alternative solutions to replace the currently widely used fluorinated substances. Several new solutions have been proposed by various companies.
[0009] CN103975107B proposes a solution using barrier coating, which mainly uses emulsion polymerization to produce hydrophilic polymer emulsion by adding emulsifier to starch, and then applies it to paper by coating. This method can also block oil and fat, but it has two problems. One is that the oil-proof effect is only achieved when the coating amount is large, and the coating amount needs to reach 6-10 grams / m2. The other is that it can only be applied to papermaking machines with coating equipment, and cannot be completed directly on the papermaking machine, so the process applicability is not strong. CN102449077B discloses that modified polyester PET resin is used and zinc stearate filler is added to form a coating material that can be applied. This method has high requirements for the application process and is expensive. CN100360612C proposes to first synthesize polysiloxane, then disperse the siloxane compound in water with an emulsifier, then add polyvinyl alcohol as an adhesive, and simultaneously add a crosslinking catalyst to allow the polysiloxane to form a polymer compound.The main solution idea is also to use coating.
[0010] CN105764980B also proposes using an acrylic ester to polymerize under cationic surfactant emulsification conditions, and then surface-treating the resulting polymer, but the oil-repellent effect is poor, the polymer cannot be retained in the pulp wet area, and there is no water- and oil-repellent effect. CN112805434A proposes using an acrylic ester to polymerize under cationic surfactant emulsification, and disperse the resulting polymer with polyether-modified silane to obtain a treatment agent. The treatment agent obtained by this method does not have good water- and oil-repellent effect, and is particularly poor in resistance to high-temperature oils and fats, and does not have a significant water- and oil-repellent effect when added to the pulp wet area. Summary of the Invention
[0011] In order to solve at least one of the technical problems existing in the prior art, the present invention provides a novel copolymer that does not contain fluorine element and has excellent water dispersibility, and a manufacturing method and application thereof, so that articles, especially fiber-based articles, can be easily treated in multiple ways to impart water and oil repellency to the articles.
[0012] In a first aspect, the present application provides a copolymer comprising a repeat unit from monomer I and a repeat unit from monomer II. a) The general formula of the structure of monomer I is: JPEG2025509434000001.jpg832 where X is selected from groups represented by X-1 and X-2, JPEG2025509434000002.jpg3744R1 and R2 are hydrogen atoms or C 1- C 20 where n is an integer from 1 to 20, for example an integer from 1 to 10, or an integer from 1 to 5; Z is selected from the structures shown below: In JPEG2025509434000003.jpg3326Z, R3 is independent of C1-C 20 Alkyl groups, C6-C 20 Aryl groups, C1-C 20 an alkoxy group or an R4-O-R5- group, where R4 is a C1-C 10R5 is an alkyl group of C1-C 10 wherein a is an alkylene group represented by the formula: Y1 and Y2 each independently represent C1-C 20 or C6-C 20 or having the structure JPEG2025509434000004.jpg3237R7 is independently 20 or C6-C 20 R8 is an aryl group of the formula: 20 Alkyl groups, C6-C 20 Aryl groups, C1-C 20 Alkoxy group or R9-OR 10 - group, where R9 is a C1-C 10 R is an alkyl group of 10 is C1-C 10 where b is an alkylene group represented by the formula: b) The general formula of the structure of monomer II is: JPEG2025509434000005.jpg744, wherein P is selected from groups represented by P-1 and P-2, JPEG2025509434000006.jpg3547 where R1 and R2 are hydrogen atoms or C1-C 20 wherein n is an integer from 1 to 20, for example an integer from 1 to 10, or an integer from 1 to 5; R3 and R4 are each independently a C1-C8 alkyl group or a benzyl group, or R3 and R4 combine together with the nitrogen atom to form a morpholino group, a piperidino group, or a pyrrolidino group.
[0013] According to some embodiments of the present invention, the mass content of repeat units from monomer I in the copolymer is 30-90%, preferably 40-85%, more preferably 50-80%.
[0014] According to some embodiments of the present invention, the mass content of the constitutional units derived from monomer II in the copolymer is 10-70%, preferably 10-40%, more preferably 15-35%.
[0015] According to some embodiments of the present invention, the repeat unit derived from monomer II is in the form of an ammonium salt or nitrogen oxide.
[0016] According to some embodiments of the present invention, in monomer I, R1 and R2 are selected from a hydrogen atom or a methyl group.
[0017] According to some embodiments of the present invention, in Z, R3 is independently selected from C1-C 10 Alkyl groups, C6-C 10 Aryl groups, C1-C 10 or an R4-O-R5- group, where R4 is a C1-C 10 is an alkyl group of 、 R5 is C1-C 10 R7 is an alkylene group represented by the formula: 10 or C6-C 10 R8 is an aryl group of the formula: 10 Alkyl groups, C6-C 10 Aryl groups, C1-C 10 or an alkoxy group of R9-OR 10 - group, where R9 is a C1-C 10 is an alkyl group of 、 R 10 is C1-C 10 and b is an alkylene group represented by the formula:
[0018] According to some embodiments of the present invention, in monomer II, R1 and R2 are selected from a hydrogen atom or a methyl group, and R3 and R4 are each independently a C1-C3 alkyl group, or R3 and R4 combine together with the nitrogen atom to form a morpholino group, a piperidino group, or a pyrrolidino group.
[0019] According to some embodiments of the invention, Z is selected from the following structures: JPEG2025509434000007.jpg121130Me represents a methyl group, ph represents a phenyl group, and 1≦m+1≦200, preferably 1≦m+1≦100, 0≦p≦200, preferably 0≦p≦100, 0≦q≦200, preferably 0≦q≦100, and 1≦x≦19, preferably 1≦x≦10.
[0020] According to some embodiments of the present invention, monomer II is one or more selected from dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminoethyl (meth)acrylate, diethylaminopropyl (meth)acrylate, dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, dipropylaminoethyl (meth)acrylamide, dimethylaminopropyl (meth)acrylamide, diethylaminopropyl (meth)acrylamide, dipropylaminopropyl (meth)acrylamide.
[0021] According to some embodiments of the present invention, the copolymer further comprises repeat units of at least one other monomer selected from monomer III, monomer IV, and monomer V; The general formula of the structure of Monomer III is: JPEG2025509434000008.jpg1150, wherein G is selected from groups represented by G-1 and G-2, In the formula, R1 represents a hydrogen atom or a methyl group, G is selected from the groups represented by G-1 or G-2, R2 is a C2-C4 alkylene group and may contain alkylene groups with different carbon numbers in one molecule, q is an integer of 1-50, and R3 is a hydrogen atom or a C1-C 20 R4 represents a hydrogen atom or a methyl group, and n is an integer of 0 to 10. Monomer IV is a monomer having an anionic group and a polymerizable unsaturated group, the anionic group being a carboxyl group or a sulfonic acid group; Monomer V is selected from a monomer containing a pyrrolidone structure and a polymerizable unsaturated group, a monomer having a blocked isocyanate group and a polymerizable unsaturated group, a monomer having an alkoxysilyl group and a polymerizable unsaturated group, or a monomer having a glycidyl group and a polymerizable unsaturated group.
[0022] According to some embodiments of the present invention, the mass content of repeat units from monomer I in the copolymer is 30-90%, preferably 40-85%, more preferably 50-80%, the mass content of repeat units from monomer II in the copolymer is 5-65%, preferably 10-40%, more preferably 15-35%, and the mass content of repeat units from other monomers in the copolymer is 1-30%.
[0023] According to some embodiments of the present invention, monomer III is one or more selected from 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxypolyethylene glycol (meth)acrylate.
[0024] According to some embodiments of the present invention, monomer IV is selected from (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, vinylsulfonic acid, (meth)allylsulfonic acid, styrenesulfonic acid, vinylbenzenesulfonic acid, acrylamido tert-butylsulfonic acid, or salts thereof.
[0025] According to some embodiments of the present invention, monomer V is selected from a monomer containing a pyrrolidone structure and a polymerizable unsaturated group, a monomer having a blocked isocyanate group and a polymerizable unsaturated group, a monomer having an alkoxysilyl group and a polymerizable unsaturated group, or a monomer having a glycidyl group and a polymerizable unsaturated group.
[0026] The mass content of repeat units from said monomers III, IV and V is 1-30%.
[0027] Furthermore, the present invention provides a treatment agent comprising the above-mentioned copolymer and a solvent, the solvent comprising water and / or an organic solvent, preferably the organic solvent being one or more of acetone, methyl ethyl ketone, 4-methyl-2-pentanone, ethyl acetate, butyl acetate, N-methyl-2-pyrrolidone, N,N-dimethylformamide, ethanol, isopropanol, n-propanol, butyl carbitol, and dipropylene glycol monomethyl ether.
[0028] Furthermore, the present invention provides a method for producing a (1) polymerizing a monomer in an organic solvent to obtain a copolymer solution; (2) optionally dispersing the copolymer solution in water and then removing the organic solvent, or removing the solvent and then dispersing the copolymer solution in water; (3) optionally, adding an acid to the copolymer solution to convert amino groups in the copolymer to ammonium salts; (4) optionally, treating the copolymer solution with an aqueous hydrogen peroxide solution to convert the amino groups to oxynitrides.
[0029] The present invention further provides a treatment method comprising treating an article to be treated with the above-mentioned copolymer or the above-mentioned treatment agent or a treatment agent produced by the above-mentioned production method, and preferably, the treatment comprises surface coating or immersion treatment.
[0030] The present invention further provides application of the above-mentioned copolymer or the above-mentioned treatment agent, or the treatment agent produced by the above-mentioned method in a surface coating or immersion treatment process for textile fabrics, leather, nonwoven fabrics, asbestos, fur, concrete, natural stone, paper, or plastic.
[0031] The present invention further provides the application of the above copolymer or the above treatment agent or the treatment agent produced by the above method in paper products, preferably said application is in surface coating, surface sizing or wet part addition of paper, paperboard and pulp moulds.
[0032] The present invention further provides a product treated with the above-mentioned copolymer, the above-mentioned treatment agent, or the treatment agent produced by the above-mentioned method, said product being a textile fabric, leather, nonwoven fabric, asbestos, fur, concrete, natural stone, paper, or plastic.
[0033] The present invention further provides a paper product comprising paper and, attached to the paper (inside and / or on its surface), the copolymer described above or the treatment described above or the treatment produced by the method described above. Effect of the Invention
[0034] The copolymer of the present invention and a treatment agent containing the same can be easily dispersed in water and can be applied to the surface treatment of various articles such as fiber fabrics, leather, nonwoven fabrics, asbestos, fur, concrete, natural stone, paper, and plastics, and the treatment methods include coating and immersion treatment, and can impart water repellency and oil repellency to the surface of the article after treatment. In particular, the copolymer of the present invention and a treatment agent containing the same can be applied to various paper treatment methods such as coating, surface sizing, and wet part addition, and can impart high water repellency and oil repellency to paper after paper treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] Monomer I has the general structural formula: JPEG2025509434000010.jpg1035 where X is selected from groups represented by X-1 and X-2, JPEG2025509434000011.jpg3953R1 and R2 are hydrogen atoms or C 1- C 20 n is an integer from 1 to 20; Z is selected from the structures shown below: In JPEG2025509434000012.jpg3328Z, R3 is independent of C1-C 20 Alkyl groups, C6-C 20 Aryl groups, C1-C 20 an alkoxy group or an R4-O-R5- group, where R4 is a C1-C 10 R5 is an alkyl group of C1-C 10 wherein a is an alkylene group represented by the formula: Y1 and Y2 each independently represent C1-C 20 or C6-C 20 or having the structure JPEG2025509434000013.jpg3235R7 is independently 20 or C6-C 20 R8 is an aryl group of the formula: 20 Alkyl groups, C6-C 20 Aryl groups, C1-C 20 Alkoxy group or R9-OR 10 - group, where R9 is a C1-C 10 R is an alkyl group of 10 is C1-C 10 and b is an alkylene group having the formula:
[0036] Specifically, R3 and R8 are C1-C 10 Alkyl groups, C1-C 10 Alkoxy groups, C6-C 10The aryl group is represented by the above formula, and the most commonly used groups are C1-C8 alkyl groups and C1-C4 alkoxy groups, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, methoxy, ethoxy, propoxy, and butoxy groups, and the aryl group is phenyl, tolyl, naphthyl, and the like. R3 and R8 are the above formula (R9-OR 10 )-, and R9 is C1-C 10 R is an alkyl group of 10 is C1-C 10 The alkylene group is CH3O(CH2), which is a relatively common one. x - etc. R7 is C1-C 20 Alkyl groups and C6-C 20 For example, the alkyl group is a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a hexadecyl group, and the like, and the aryl group is a phenyl group, a tolyl group, a naphthyl group, and the like.
[0037] For example, Z is typically selected from the following structures: JPEG2025509434000014.jpg134140Me represents a methyl group, ph represents a phenyl group, and 1≦m+1≦200, preferably 1≦m+1≦100, 0≦p≦200, preferably 0≦p≦100, 0≦q≦200, preferably 0≦q≦100, and 1≦x≦19, preferably 1≦x≦10.
[0038] The general formula of the structure of Monomer II is: JPEG2025509434000015.jpg1052, where P is selected from groups represented by P-1 and P-2, JPEG2025509434000016.jpg3443 where R1 and R2 are hydrogen atoms, C1-C 20wherein n is an integer from 1 to 20; R3 and R4 are each independently a C1-C8 alkyl group or a benzyl group, or R3 and R4 combine with the nitrogen atom to form a morpholino group, a piperidino group, or a pyrrolidino group.
[0039] R3 and R4 are preferably an alkyl group having 1 to 8 carbon atoms, particularly preferably a methyl group or an ethyl group.
[0040] The polymerized units in the polymer derived from the amino monomer II may be of one type or more types.
[0041] Examples of amino monomers II are dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminoethyl (meth)acrylate, diethylaminopropyl (meth)acrylate, dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, dipropylaminoethyl (meth)acrylamide, dimethylaminopropyl (meth)acrylamide, diethylaminopropyl (meth)acrylamide, dipropylaminopropyl (meth)acrylamide, etc.
[0042] The nitrogen in the amino monomer is a tertiary nitrogen atom, which can be converted into an amine oxide under oxidizing agent conditions, and can also be converted into a cationic ammonium salt by adding an acid, which further improves the performance of the polymer, such as aqueous solubility stability.
[0043] The amino monomer II includes the following: CH2=C(R)COO(CH2)2N(CH3)2, CH2=C(R)COO(CH2)3N(CH3)2, CH2=C(R)COO(CH2)2N(CH2CH3)2, CH2=C(R)COO(CH2)3N(CH2CH3)2, CH2=C(R)COOCH2CH(OH)CH2N(CH3)2, CH2=C(R)COOCH2CH(OH)CH2N(CH2CH3)2, CH2=C(R)-CONH(CH2)2N(CH3)2, CH2=C(R)-CONH(CH2)3N(CH3)2, CH2=C(R)-CONH(CH2)2N(CH2CH3)2, CH2=C(R)-CONH(CH2)3N(CH2CH3)2, In the formula, R is a hydrogen atom or an alkyl group containing C1-C4.
[0044] The repeating unit having an ammonium salt can be produced by a reaction of adding an acid. Examples of the acid include inorganic acids (e.g., hydrogen halides (hydrochloric acid, hydrogen bromide, or hydrogen iodide)), sulfuric acid, nitric acid, and organic acids, such as formic acid, acetic acid, glycolic acid, malic acid, citric acid, and itaconic acid. Organic acids are more commonly used, and because they have small molecules, formic acid and acetic acid are highly volatile and have a strong odor. The amount of acid added can be 10% to 200% molar equivalents relative to 1 molar equivalent of amino group in the repeating unit II having an amino group, and is most commonly 100% molar equivalent relative to the molar equivalent of ammonia in the monomer II.
[0045] Monomer II can also be converted to an N-oxide by reaction with a peroxide, and examples of the oxidizing agent include hydrogen peroxide, persulfuric acid, and peroxycarboxylic acids such as m-chloroperbenzoic acid. The amount of the oxidizing agent added can be 5% to 100% molar equivalents relative to 1 molar equivalent of the amino group in the repeating unit II having an amino group, and is most commonly 50% molar equivalents.
[0046] It is preferable that the amino group of the repeating unit II derived from an amino monomer is modified to an ammonium salt or an N-oxide. The repeating unit II derived from an amino monomer is preferably (i) ammonium salts, (ii) N-oxides, (iii) a combination of an ammonium salt and an N-oxide; In the combination (iii), the molar equivalent ratio of the ammonium salt to the N-oxide may be 1:9-9:1.
[0047] As the monomer III, the following compounds are preferred: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxypolyethylene glycol (meth)acrylate, etc., their typical structural formulas are as follows: CH2=C(R)-C(O)-O-CH2CH2OH, CH2=C(R)-C(O)-(CH2CH2O)2H, CH2=C(R)-C(O)-O-(CH2CH2O)3H, CH2=C(R)-C(O)-O(CH2CH2O) 11 H, CH2=C(R)-C(O)-O-(CH2CH2O) 12 H, CH2=C(R)-C(O)-N(R)-CH2OH CH2=C(R)-C(O)O-CH2CH2OCH3, CH2=C(R)-C(O)O-CH2CH2OCH2CH3, CH2=C(R)-C(O)O-CH2CH2OCH3, CH2=C(R)-C(O)O-CH2CH2OCH2CH3, In the formula, R is a hydrogen atom or an alkyl group containing 1 to 4 carbon atoms.
[0048] Monomer IV is a monomer having an anionic group and a polymerizable unsaturated group, and the anionic group may be a carboxyl group or a sulfonic acid group. Among them, (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, vinylsulfonic acid, (meth)allylsulfonic acid, styrenesulfonic acid, vinylbenzenesulfonic acid, acrylamido tert-butylsulfonic acid or salts thereof are included. The most common one is (meth)acrylic acid.
[0049] Monomer V: The excellent performance polymer of the copolymer further comprises monomer V, Monomer V is selected from monomers containing a pyrrolidone structure and a polymerizable unsaturated group, and monomers having a blocked isocyanate group, an alkoxysilyl group, a glycidyl group, and a polymerizable unsaturated group.
[0050] Examples of the monomer containing a pyrrolidone structure and a polymerizable unsaturated group include N-vinyl-2-pyrrolidone, N-vinyl-3-methyl-2-pyrrolidone, N-vinyl-4-methyl-2-pyrrolidone, N-vinyl-5-methyl-2-pyrrolidone, and N-vinyl-3,3-dimethyl-2-pyrrolidone.
[0051] Examples of the monomer having a blocked isocyanate and a polymerizable unsaturated group include the following compounds. 2-isocyanatoethyl (meth)acrylate with 2-butanone oxime, 2-isocyanatoethyl (meth)acrylate with pyrazole, 2-isocyanatoethyl (meth)acrylate with 3,5-dimethylpyrazole, 2-isocyanatoethyl (meth)acrylate with 3-methylpyrazole, 2-isocyanatoethyl (meth)acrylate with ε-caprolactam, 3-isocyanatoethyl (meth)acrylate with 2-butanone oxime, 3-isocyanatoethyl (meth)acrylate with pyrazole, 3-isocyanatoethyl (meth)acrylate with 3, Examples of the polyisocyanatoethyl (meth)acrylate include 5-dimethylpyrazole adduct, 3-isocyanatoethyl (meth)acrylate and 3-methylpyrazole adduct, 3-isocyanatoethyl (meth)acrylate and ε-caprolactam adduct, 4-isocyanatoethyl (meth)acrylate and 2-butanone oxime adduct, 4-isocyanatoethyl (meth)acrylate and pyrazole adduct, 4-isocyanatoethyl (meth)acrylate and 3,5-dimethylpyrazole adduct, 4-isocyanatoethyl (meth)acrylate and 3-methylpyrazole adduct, and 4-isocyanatoethyl (meth)acrylate and ε-caprolactam adduct.
[0052] Examples of monomers having an alkoxysilyl group and a polymerizable unsaturated group include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyldimethoxymethylsilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyldiethoxyethylsilane, and allyltrimethoxysilane.
[0053] Examples of the monomer having a glycidyl group and a polymerizable unsaturated group include glycidyl (meth)acrylate.
[0054] In the present invention, the mass content of monomer I may be non-uniform from 30% to 90%, for example, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., preferably 40-85%, more preferably 50-80%; The mass content of monomer II may vary from 5% to 65%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, etc., preferably 10-40%, more preferably 15-35%.
[0055] In the present invention, the content of monomer I may be non-uniformly between 30% and 90%, for example, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., preferably 40%-85%, more preferably 50-80%, and its main function is to provide water and oil repellency.
[0056] The content of monomer II may be in the range of 10-70%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, etc., preferably 10-40%, more preferably 15-35%, and its main function is to provide water solubility and positive charge to the polymer.
[0057] The content of monomer III may be in the range of 1-30%, for example, 1%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, etc., which can improve the affinity with fibers, and is preferably 1-15%.
[0058] The content of monomer IV may be in the range of 1-30%, for example, 1%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, etc., which can improve the water solubility of the polymer, and is preferably 1-15%.
[0059] The content of monomer V may be in the range of 1-30%, for example, 1%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, etc., which can improve some performances of the polymer, and is preferably 1-15%.
[0060] The weight average molecular weight of the copolymer produced by the above I-IV monomers of the present invention may be 1,000-1,000,000, preferably 4,000-500,000. The weight average molecular weight can be measured by gel chromatography in terms of polystyrene.
[0061] The polymerization method for the present copolymer is not particularly limited, and any of the conventional radical polymerization methods, for example, bulk polymerization, solution polymerization in an organic solvent, and emulsion polymerization in water, can be used.
[0062] In the present invention, after polymerization (for example, solution polymerization or emulsion polymerization), it is preferable to add water and then remove the solvent to obtain an aqueous dispersion, or it is also possible to remove the solvent and then add water to obtain an aqueous dispersion.
[0063] The organic solvent may be selected from ketones, esters, and alcohols, such as acetone, methyl ethyl ketone, 4-methyl-2-pentanone, ethyl acetate, butyl acetate, N-methyl-2-pyrrolidone, N,N-dimethylformamide, ethanol, isopropanol, n-propanol, butyl carbitol, dipropylene glycol monomethyl ether, and the like, which may be used alone or in combination.
[0064] As an emulsifier for emulsifying by adding water after emulsion polymerization or solution polymerization, various general-purpose anionic, cationic and nonionic emulsifiers can be used.
[0065] As the polymerization initiator, a peroxide, an azo compound or a persulfate compound can be used, and as the polymerization initiator, an oil-soluble or water-soluble initiator can be used depending on the polymerization system.
[0066] Preferred examples of the oil-soluble polymerization initiator include 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 1,1'-azobis(cycloethane-1-carbonitrile), dimethyl-2,2'-azobis(2-methylpropionate), benzoyl peroxide, di-t-butyl peroxide, lauroyl peroxide, cumene hydroperoxide, t-butyl peroxypivalate, and diisopropyl peroxydicarbonate.
[0067] Preferred examples of the water-soluble polymerization initiator include 2,2'-azobisisobutylamidine dihydrochloride, 2,2'azobis(2-methylpropionamidine) hydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] hydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] sulfate hydrate, 2,2'-azobis[2-(5-methyl-imidazolin-2-yl)propane] hydrochloride, potassium persulfate, barium persulfate, ammonium persulfate, hydrogen peroxide, and t-butyl hydroperoxide.
[0068] As the polymerization initiator, peroxides or azo compounds having a half-life of 10 hours and a decomposition temperature of 40° C. or higher, such as t-butyl peroxypivalate and 2,2′-azobis(2,4-dimethylvaleronitrile), are preferred.
[0069] The amount of the initiator added is 0.1 to 5 parts by weight per 100 parts by weight of the monomer.
[0070] In the polymerization process, if necessary, a certain amount of molecular weight regulator may be added, and common examples are mercapto compounds such as 2-mercaptopropionic acid, 2-mercaptoethanol, alkyl mercaptan, mercaptopropionic acid, etc. The amount of the molecular weight regulator added is 0-10 parts, preferably 0.01-5 parts, based on 100 parts by weight of the monomer.
[0071] The typical solution polymerization process of the present invention is to first add a solvent, then add and dissolve the corresponding monomer, introduce nitrogen gas to replace the oxygen therein, add an initiator, and then heat to a reaction temperature of 40-120°C, and the reaction time varies from 4-20 hours.
[0072] Another common polymerization method is emulsion polymerization, which can be polymerized by emulsifying the monomer with an emulsifier. First, the monomer and emulsifier are added to water, and then emulsified by stirring. Then, nitrogen gas is introduced to replace the gas, and a water-soluble initiator is added. The reaction temperature is then heated to 40-90°C, and the reaction time is 4-20 hours, which varies.
[0073] In order to obtain a stable polymer dispersion, a high-pressure homogeneous emulsifier or ultrasonic dispersing device can be used to strongly disperse and emulsify the polymer system, turn the monomer into a very stable emulsion particle, and then start polymerization. As for the widely used emulsifier, the available varieties include anionic, cationic or nonionic, and the amount of emulsifier used is 0.5-10 parts by weight for 100 parts by weight of monomer. Generally, it is 1-5 parts by weight.
[0074] The treatment agent of the present invention is in the form of a solution or emulsion. The treatment agent contains a copolymer, water and an organic solvent, and the content of the copolymer in the treatment agent is 1-50% by weight of effective part, preferably 2-30% by weight.
[0075] The process for producing the treatment agent of the present invention is as follows. (1) Monomers I, II, and optional monomers III, IV, and V are placed in an organic solvent in a certain ratio, and an initiator is added to polymerize. (2) If necessary, after the polymerization is completed, water is added to disperse the mixture and the organic solvent is removed, or the solvent is removed and then water is added to disperse the mixture. (3) If necessary, a step of converting the amino groups in the polymer into ammonium salts by adding an acid. (4) If necessary, an oxidizing agent is added to the above dispersion to carry out an oxidation treatment.
[0076] The organic solvent in the polymer solution can be removed by vacuum distillation under heating. The temperature may be controlled to 40°C or higher, preferably 60-120°C. Water may be added to disperse the polymer and then the solvent may be removed, or the solvent may be removed and then water may be added to disperse the polymer. The amount of water added may be 100-2000 parts per 100 parts by weight of the polymer.
[0077] The amino group contained in the monomer II can be converted to an N-oxide by adding an oxidizing agent, the amount of which is 0.1-10 parts per 100 parts by weight of the polymer.
[0078] The articles to be treated that can use the aqueous dispersion type treatment composition of the present invention are not particularly limited, and include textile fabrics, leather, nonwoven fabrics, asbestos, fur, concrete, natural stone, paper, plastics, and other textile fabrics, of which the effects are particularly good for textile fabrics, paper, and natural stone.
[0079] The composition solution formed by the copolymer of the present invention can treat paper. The paper that is mainly treated covers almost all types of paper, from paper boxes with a unit area (m2) of 300 grams, to craft paper with a unit area (m2) of 80 grams, to tissue paper with a unit area (m2) of 100 grams, to paper plastic products with a unit area (m2) of 200 grams.
[0080] The raw material for the paper may be chemically bleached or unbleached pulp, groundwood pulp, chemi-mechanical pulp, mechanical pulp, etc., and resin components such as polyamide, polyolefin, polyvinyl alcohol, etc. may be added to these pulp plates.
[0081] Sizing agents may be added to these papers to improve the water repellency of the paper, and commonly used sizing agents include cationic rosin gum, anionic rosin gum, alkyl ketene dimer (AKD)-based sizing agents, alkenyl succinic anhydride ASA-based sizing agents, and cationic styrene acrylate emulsions, etc. The amount of sizing agent used may be 0.01-5% by weight of the pulp weight.
[0082] In addition to sizing agents, other adjuvants may be added to improve the performance of the paper, such as modified starch, carboxymethyl cellulose, epichlorohydrin modified polyamide enhancers, retention aids, dyes, brighteners, air entraining agents, defoamers, and other adjuvants added to paper manufacture.
[0083] Examples of fiber fabrics include natural fibers of animal or plant origin, such as cotton, hemp, wool, and silk; synthetic fibers, such as polyamide, polyester, polyvinyl alcohol, polyacrylonitrile, polyvinyl chloride, and polypropylene; semi-synthetic fibers, such as rayon and acetate fibers; inorganic fibers, such as glass fibers, carbon fibers, and rock wool fibers; and mixed fiber fabrics thereof.
[0084] Fiber fabric measurement method - Fabric processing The textiles treated in this study may be dyed 100% polyester fabric and 100% khaki drill fabric, and roll samples were immersed in a 3% aqueous solution of the treatment composition of the present invention (pickup rate 60%) and then dried for 3 minutes at 130° C. The water and oil repellency of the resulting sample fabrics was evaluated.
[0085] Fiber and fabric measurement method - Water resistance According to the Teflon global standard and quality control measurement method, the sample fabric was measured and observed with different volumetric contents of isopropyl alcohol to confirm the degree of surface wetting. This measurement provided a rough index of water stain resistance. The higher the water resistance level, the better the resistance of the final substrate to water-based substances. The composition of the standard measurement solution is shown in Table 1 below.
[0086] JPEG2025509434000017.jpg89155
[0087] Fiber and fabric measurement method - Spray measurement Dynamic water resistance of treated substrates was measured according to American Association of Textile Chemists and Colorists (AATCC) TM-22 and referenced published standards. A score of 100 indicates that there is no adhesion or wetting of the surface. 90 points indicates slight adhesion wetting. 80 points, sample indicates spray point is wet. A score of 70 indicates that the sample is partially wet on the top surface. A score of 50 indicates that the sample is completely wet on the top surface. A score of 0 indicates that the sample was completely wet on both the top and bottom surfaces.
[0088] The smaller the value, the more gradually the wetting and penetration spreads.
[0089] Fiber and fabric measurement method - Oil resistance The oil resistance is evaluated according to the test method of AATCC-TM118, the basic principle of which is to use measuring oils with different surface tensions to drop on the measuring cloth, the higher the level, the better the oil resistance. The composition of the standard measuring liquid is shown in Table 2 below.
[0090] JPEG2025509434000018.jpg91158
[0091] Paper Processing and Measurement Methods The types of paper that can be processed include tissue paper, cardboard, paperboard, and pulp molds, and it is possible to process paper boxes with an area of 300 grams per unit (square meter), kraft paper with an area of 80 grams per unit (square meter), tissue paper with an area of 100 grams per unit (square meter), and paper-plastic products with an area of 200 grams per unit (square meter).
[0092] The raw material of the paper can be chemically bleached or unbleached pulp, groundwood pulp, chemical mechanical pulp, mechanical pulp, etc., and resin components such as polyamide, polyolefin, polyvinyl alcohol, etc. can also be added to these pulp plates. The paper processing method is as follows. (1) Surface coating example: Preparation of test paper: Paper weight 230 g / m2 The paper is composed of five layers, of which the bottom and top layers are made of chemical pulp plate LBKP (broadleaf bleached kraft pulp) plus NBKP (softwood bleached kraft pulp) in a ratio of 7:3, and the middle three layers are made of chemical mechanical pulp or mechanical pulp plate, which are compounded on the paper machine into a board with a weight of 230g / m2. The coating starch used was tapioca coating starch MS-1 manufactured by Guangxi Mingyang Yang Biochemical Co., Ltd. The starch concentration was 20%, and the starch was added with water and heated to over 90°C to gelatinize it. After gelatinization was complete, the starch was added to the synthesized paper treatment agent, resulting in a concentration of 1-20%. The starch temperature was controlled to over 50°C, and the top layer of the paperboard was coated with a paper coater, with a coating amount of 3-8 grams per square meter. (2) Surface size processing example: Preparation of test paper: Paper weight 50 grams / m2 Chemical pulp plate LBKP (broadleaf bleached kraft pulp) and NBKP (softleaf bleached kraft pulp) were added in a ratio of 5:5, and the pulp plate was beaten to a Canadian standard freeness of 200ml. In the papermaking process, cationic starch MC-2 type starch manufactured by Guangxi Mingyang Yang Biochemical Co., Ltd. was added in an amount of 2% by weight of the pulp plate, and the paper was made on a fourdrinier machine to obtain tissue paper weighing 50g / m2. The starch solution used was non-ionic modified starch hydroxyethyl starch, Penford Gum 290 starch manufactured by Penford, with a concentration of 5%. First, the starch solution was heated to 90°C or higher to gelatinize it, and after gelatinization was completed, a synthesized treatment agent was added to it, with a concentration of 1-20% by weight. The temperature of the starch solution was controlled to 70°C or higher, and the paper was first subjected to a surface sizing treatment, the amount of liquid absorption exceeded 70%, and then a drying treatment was performed to obtain treated paper. (3) Wet part processing: Paper plastic weight 350g / m2 Sugarcane pulp plate was directly crushed, the beating degree was 600 ml of Canadian standard freeness, and the pulp concentration was 0.3%. An alkyl ketene dimer (AKD) sizing agent was added in an amount of 2% of the pulp weight, and a synthetic treatment agent was further added in an amount of 1-20%. The pulp was placed in a 10-inch disk mold filter at a given weight, and the moisture was removed by vacuum suction. The disk was dried in the mold at 150°C for 120 seconds, and the water and oil repellency of the disk was evaluated.
[0093] Water and oil repellency evaluation The following examples and comparative examples will specifically explain the present invention, but are not intended to limit the present invention. In the following experiments, unless otherwise specified, all percentages of added amount are parts by weight.
[0094] The test methods used below are as follows: Oil repellency measurement evaluation (1) Oil repellency evaluation TAPPI test kit Oil repellency (kit method) was measured in accordance with TAPPI T-559cm-02. For the test, a test agent made by mixing castor oil, toluene, and n-heptane in the volume ratio shown in the table below was used, and the test results were indicated by numbers; the higher the number, the better the oil repellency. The treated paper was placed on a flat, uncontaminated surface, and the test agent was dropped onto the surface of the paper. After leaving it on for 15 seconds, the test agent was wiped off with absorbent paper and observed for penetration. If there was no penetration, it was deemed a pass, and a higher level of measurement was performed. The measuring agent was prepared according to the composition shown in Table 3.
[0095] JPEG2025509434000019.jpg101158
[0096] (2) Heat-resistant oil measurement The treated paper was made into a container capable of holding liquid, and 85℃ hot oil (salad oil, peanut oil, rapeseed oil) was poured into the paper container, and the container was observed for 20 minutes to confirm the presence or absence of penetration, and was ranked and scored. This type of measurement method is mainly applied to the pulp molding industry. Five points showed no surface discoloration. Four pieces had slight surface discoloration. Three of the samples showed surface discoloration and slight penetration. Two points were seriously penetrating. One leak was particularly severe and slowly dripped oil. A score of 0 indicates a particularly severe leak where the oil dripped relatively quickly.
[0097] Water repellency evaluation - Cobb measurement (1) Cobb measurement This measurement is performed according to GB / T1540-2002 or ISO 535:1991, and the principle is to support 10 mm of water at a height of 100 cm. 2 The amount of water absorbed by the paper in one minute (g) was measured and expressed as the weight per square meter (g / m 2 ) The Cobb absorbency tester is usually an inverted cylinder tester. The metal cylinder is a cylindrical body, and its internal cross-sectional area is generally (100±0.2) cm 2 and the corresponding inner diameter is (112.8±0.2)mm. If a cylinder with a small area is used, the recommended area is 50cm or more, in which case the volume of water should be reduced accordingly to ensure a water liquid height of 10mm. The cylinder height is 50mm, and the part of the annular surface of the cylinder that contacts the sample is smooth and has sufficient roundness to prevent the sample from being damaged by the cylinder edge. To prevent water leakage, a layer of elastic but water-absorbent rubber pad or gasket should be added to the inverted cylinder cover and the flat pressure base, and the roller width of the metal pressure roller should be (200±0.5)mm, the mass should be (10±0.5)kg, and the surface should be smooth. The treated paper sample was cut into 10 pieces (5 pieces on each side) of (125±5) mm square or (125±5) mm circular samples. For instruments with a small measurement area, the size of the sample should be slightly larger than the outer diameter of the cylinder to avoid water leakage due to the sample being too small, and also to avoid the influence on the operation due to the sample being too large. Before placing the sample, it should be ensured that the cylinder annular surface and rubber pad that contact the sample are dry, and hands should not touch the measurement area. After taking 100mL of water in a graduated cylinder and putting it into the cylinder, the weighed sample was placed on the annular surface of the cylinder with the measurement surface facing down. The presser lid was placed on the sample and clamped to fix it to the cylinder. The cylinder was inverted 180°, the stopwatch was turned on at the same time, and the sample was allowed to absorb water for 60 seconds. 10s to 15s before the end of the absorption, the cylinder was turned over, the holding lid clamp device was loosened, and the sample was removed. The measurement water must be replaced every 5 measurements to avoid affecting the measurement results. At the moment the specified absorption time was reached, the sample removed from the cylinder was placed on the absorbent paper laid out in advance, with the absorbent side facing down. After placing a sheet of absorbent paper on the top of the sample, it was immediately roll pressed once back and forth within 4s without applying any other pressure with a metal press roll, and the water remaining on the sample surface was absorbed and dried. The sample was quickly removed, the absorbent side was folded back, and then folded back again and weighed, with an accuracy of up to 0.001g. In some cases, the sample is difficult to fold with thick cardboard, and in this case the second weighing should be done quickly. The Cobb value is expressed by the following formula: C=(g2-g1) / F where C is the cobb value, g2 is the weight of the sample after water absorption, g1 is the weight of the sample before water absorption, F is 100cm 2 is the measured area.
[0098] (2) Hot water resistance test This method directly measures the hot water resistance of paper, and the measurement method is relatively simple. Generally, the treated paper is placed in a container capable of holding liquid, and 100°C hot water is poured into it, and the paper is observed for 30 minutes to see if there are any leaks. If there are no leaks, the paper is deemed to have passed the test. This method is applicable to pulp molded products. Stone processing and measurement methods: Natural stone materials that can be treated include marble, granite, sandstone, slate, and the like. Taking sandstone as an example, the treatment agent of the present invention was diluted with water to a 3% liquid, a sandstone sample was taken and immersed in the liquid, then taken out, naturally dried for 48 hours, and the temperature was raised to 25°C or higher. Then, salad oil, mustard jam, coffee, vinegar, etc. were dropped onto the surface of the sandstone, and the wet state was observed. If there was no penetration, it indicated good resistance. Five points showed no surface discoloration. Four pieces had slight surface discoloration. Three of the samples showed surface discoloration and slight penetration. Two points were seriously penetrating.
[0099] Example 1 A 500 ml four-neck flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer was charged with 80 g of CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 (molecular weight 500, referred to as Si-5), 20 g of dimethylaminoethyl methacrylate CH2=C(CH3)C(O)-O-CH2CH2N(CH3)2 (referred to as DM), and 100 g of methyl ethyl ketone (hereinafter referred to as MEK). Nitrogen gas was introduced for 30 minutes, and the temperature was gradually raised to 50-60°C. 1.4 g of tert-butyl peroxypivalate, a peroxide initiator, was added in portions, and the reaction temperature was controlled at 60°C for 20 hours to obtain approximately 200 g of polymer A solution, with a solid content of approximately 50%. When the solution was measured using a gas chromatograph mass spectrometer, the residual mass concentration of each monomer was less than 0.1%, indicating that the monomer composition of the obtained polymer was almost identical to the monomer composition added. 295 g of water and 5.8 g of glacial acetic acid were added, and the mixture was stirred while keeping at 70° C. for 1 hour or more, and MEK in the polymer A solution was distilled off under reduced pressure to obtain an aqueous dispersion with a solid content of 25%.
[0100] Examples 2-4 The process adopted in Examples 2-4 is completely the same as that in Example 1, but monomers I CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 with different molecular weights were adopted, and synthesis experiments were carried out with Si-10 (molecular weight 1000), Si-20 (molecular weight 2000), and Si-30 (molecular weight 3000), respectively, and the residual mass concentration of each monomer was measured with a gas chromatograph mass spectrometer, and it was shown that the monomer composition of the obtained polymer was almost the same as the monomer composition added.
[0101] The performance measurements of Examples 1 to 4 were carried out by selecting three methods for each. (1) Surface coating treatment: Weight is 230g / m 2 Ten sheets of white card paper were prepared, and a starch gelatinization solution (20% concentration) was added to the copolymer treatment agent (5%) and applied to the surface. The oil repellency of the paper was measured using the TAPPI level, and the water repellency was measured using the Cobb value method. (2) Surface size treatment: weight is 50g / m 2 Ten sheets of paper were prepared and surface-sized with a solution of starch (6%) and copolymer treatment agent (5%). The oil repellency of the paper was measured using the TAPPI level, and the water repellency was measured using the Cobb value method. (3) Wet treatment: A pulp solution with a concentration of 1% was prepared, and 2% of an alkylketene dimer (AKD) type sizing agent and 10% of a treatment agent were added to the weight of a dry pulp plate to prepare a 10-inch disk weighing 20 g. Measurements were performed for 20 minutes in salad oil at 85°C, and rankings and scores were given according to the degree of penetration. Measurements were performed for 30 minutes in hot water at 100°C, and a pass or water leakage was recorded. The performance is summarized in Table 4.
[0102] JPEG2025509434000020.jpg90157
[0103] Examples 5-8 The process adopted in Examples 5-8 is completely the same as that of Example 1, but the content of monomer I is different, all of which are in the range of 30-80%, and the content of amino group-containing monomer II is adjusted accordingly. The polymer solution obtained by gas chromatography mass spectrometry shows that the residual mass concentration of each monomer is less than 0.1%, and the monomer composition of the obtained polymer is almost the same as the monomer composition added. The performance measurement method is the same as that of Example 1, and the performance is summarized in Table 5.
[0104] JPEG2025509434000021.jpg104170
[0105] Examples 9-13 The process employed in Examples 9-13 was exactly the same as that in Example 1, but synthesis experiments were carried out using different monomers I, and the polymer solutions obtained by measurement using a gas chromatograph mass spectrometer showed that the residual mass concentrations of each monomer were all less than 0.1%, indicating that the monomer composition of the obtained polymer was almost identical to the monomer composition added. Example 9 The structure of Monomer I is CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)3 (molecular weight 500), and is designated as Si-5Me. Example 10 The structure of Monomer I is CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C8H 17 (molecular weight 500) and is represented as Si-5Oct. Example 11 The structure of Monomer I is CH2=C(CH3)C(O)-(NH)-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 (molecular weight 500), and is represented as Si-5Bu(N). Example 12 The structure of Monomer I is CH2=C(CH3)C(O)-O-(CH2)3Si(CH3)[(Si(CH3)2O]n-Si(CH3)2C4H9]2 (molecular weight 500), and is designated as Si-5-2Bu. Example 13 The structure of Monomer I is CH2=C(CH3)C(O)-O-(CH2)3Si(CH3)[(Si(CH3)2O]n-Si(CH3)2(CH2)3OCH3]2 (molecular weight 500), and is designated as Si-5-2OMe. The measurement method was the same as in Example 1, and the performance is summarized in Table 6.
[0106] JPEG2025509434000022.jpg82170
[0107] Example 14 A 500 ml four-neck flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer was charged with 80 g of CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 (molecular weight 500) (referred to as Si-5), 20 g of N-[3-(dimethylamino)propyl]-2-methyl-2-acrylamide CH2=C(CH3)C(O)-NH-CH2CH2CH2N(CH3)2 (referred to as DN), and 100 g of methyl ethyl ketone (hereinafter referred to as MEK). Nitrogen gas was introduced for 30 minutes, and the temperature was gradually raised to 50-60°C. 1.4 g of tert-butyl peroxypivalate, a peroxide initiator, was charged in portions, and the reaction temperature was controlled at 60°C for 20 hours to obtain approximately 200 g of polymer A solution, with a solid content of approximately 50%. The obtained polymer solution was measured using a gas chromatograph mass spectrometer, and the residual mass concentration of each monomer was found to be less than 0.1%, indicating that the monomer composition of the obtained polymer was almost identical to the monomer composition added. 295 g of water and 5.8 g of glacial acetic acid were added, and the mixture was stirred while keeping at 70° C. for 1 hour or more, and MEK in the polymer A solution was distilled off under reduced pressure to obtain an aqueous dispersion with a solid content of 25%.
[0108] Example 15 A 500 ml four-neck flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer was charged with 80 g of CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 (molecular weight 500) (referred to as Si-5), 20 g of N-[3-(dimethylamino)propyl]-2-methyl-2-acrylamide CH2=C(CH3)C(O)-NH-CH2CH2CH2N(CH3)2 (referred to as DN), and 100 g of methyl ethyl ketone (referred to as MEK). Nitrogen gas was introduced for 30 minutes, and the temperature was gradually raised to 50-60°C. 1.4 g of tert-butyl peroxypivalate, a peroxide initiator, was added in portions, and the reaction temperature was controlled at 60°C for 20 hours to obtain approximately 200 g of polymer A solution, with a solid content of approximately 50%. The obtained polymer solution was measured using a gas chromatograph mass spectrometer, and the residual mass concentration of each monomer was found to be less than 0.1%, indicating that the monomer composition of the obtained polymer was almost identical to the monomer composition added. 244 g of water and 5.8 g of glacial acetic acid were added, and the mixture was stirred and kept warm at 70° C. for 1 hour or more. MEK in the polymer A solution was distilled off under reduced pressure, and 50 g of 1% hydrogen peroxide (H2O2) was added. The mixture was kept warm for 1 hour or more, and the solution was cooled to obtain an aqueous dispersion with a solid content of 25%.
[0109] Example 16 A 500 ml four-neck flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer was charged with 80 g of CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 (molecular weight 500) (referred to as Si-5), 20 g of N-[3-(dimethylamino)propyl]-2-methyl-2-acrylamide CH2=C(CH3)C(O)-NH-CH2CH2CH2N(CH3)2 (referred to as DN), and 100 g of methyl ethyl ketone (referred to as MEK). Nitrogen gas was introduced for 30 minutes, and the temperature was gradually raised to 50-60°C. 1.4 g of tert-butyl peroxypivalate, a peroxide initiator, was added in portions, and the reaction temperature was controlled at 60°C for 20 hours to obtain approximately 200 g of polymer A solution, with a solid content of approximately 50%. The obtained polymer solution was measured using a gas chromatograph mass spectrometer, and the residual mass concentration of each monomer was found to be less than 0.1%, indicating that the monomer composition of the obtained polymer was almost identical to the monomer composition added. 270 g of water and 5.8 g of glacial acetic acid were added, and the mixture was stirred and kept at 70°C for 1 hour or more, and MEK in the polymer A solution was distilled off under reduced pressure. 25 g of 1% hydrogen peroxide (H2O2) was further added, and the mixture was kept at 70°C for 1 hour or more. After the solution was cooled, an aqueous dispersion with a solid content of 25% was obtained. The measurement methods for Examples 14-16 were the same as those for Example 1, and the performances are summarized in Table 7.
[0110] JPEG2025509434000023.jpg101137
[0111] Example 17 Into a 500-mL four-neck flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer, add 77 g of CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 (molecular weight 500, denoted as Si-5), 15 g of dimethylaminoethyl methacrylate CH2=C(CH3)C(O)-O-CH2CH2N(CH3)2 (denoted as DM), 15 g of hydroxyethyl methacrylate CH2=C 8 g of (CH3)-C(O)-O-CH2CH2OH (hereinafter referred to as HEMA) and 100 g of methyl ethyl ketone (hereinafter referred to as MEK) were charged, nitrogen gas was passed for 30 minutes, the temperature was gradually raised to 50-60°C, 1.4 g of tert-butyl peroxypivalate, a peroxide initiator, was charged in portions, the reaction temperature was controlled at 60°C, and the reaction was carried out for 20 hours to obtain about 200 g of polymer A solution, with a solid content of about 50%. When the solution was measured using a gas chromatograph mass spectrometer, the residual mass concentrations of each monomer were all less than 0.1%, of which the residual concentration of HEMA was less than 0.05%, indicating that the monomer composition of the obtained polymer was almost the same as the monomer composition added. 295 g of water and 5.8 g of glacial acetic acid were added, and the mixture was stirred while keeping at 70° C. for 1 hour or more, and MEK in the polymer A solution was distilled off under reduced pressure to obtain an aqueous dispersion with a solid content of 25%.
[0112] Examples 18-20 The process adopted in Examples 18-20 was the same as that in Example 17, except that the synthesis experiments were carried out using monomers I CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 with different molecular weights. Monomer I was represented as Si-10 (molecular weight 1000), Si-20 (molecular weight 2000), and Si-30 (molecular weight 3000), respectively, and the solution was measured using a gas chromatograph mass spectrometer, and the remaining mass concentration of each monomer was less than 0.1%, of which the remaining concentration of HEMA was less than 0.05%, indicating that the monomer composition of the obtained polymer was almost the same as the monomer composition added.
[0113] The performance measurement methods for Examples 17 to 20 are as follows. 1) Fabric measurements: 100% polyester fabric and 100% cotton fabric were selected, the treatment agent was diluted to 3% liquid, and immersion roll treatment was carried out to measure water resistance, spray test and oil resistance. 2) Paper measurement: Select two types of paper, one is 230g / m 2 The card paper was 50 g / m2 and had a surface coating treatment with a concentration of 5%. 2 The paper was thin and was treated by surface sizing, with the concentration of the treatment agent being 5%. The TAPPI oil resistance level and Cobb water absorption value were measured respectively. 3) Measurement of paper tableware: A pulp solution with a concentration of 1% was prepared, 2% AKD type sizing agent and 10% treatment agent were added, and the dish was made into a 10-inch dish with a weight of 20g. It was measured for 20 minutes in salad oil at 80°C, and ranked and scored according to the degree of penetration. It was measured for 30 minutes in hot water at 100°C, and recorded as pass or water leakage. 4) Sandstone measurement: The treatment agent of the present invention was diluted with water to a 3% liquid, and a sandstone sample was taken and immersed in the liquid. After taking it out, it was naturally dried for 48 hours and the temperature was increased to 25°C or higher. After that, salad oil, mustard jam, and coffee were dropped onto the surface of the sandstone, and the wet state was observed, ranked, and scored. The performance is summarized in Table 8.
[0114] JPEG2025509434000024.jpg124165
[0115] Examples 21-24 The process adopted in Examples 21-24 was the same as that in Example 17, except that the content of monomer I was not uniform, ranging from 30% to 80%, and the content of amino-containing monomer II was adjusted accordingly. The polymer solution was measured using a gas chromatograph mass spectrometer, and the residual mass concentration of each monomer was less than 0.1%, of which the residual concentration of HEMA was less than 0.05%, indicating that the monomer composition of the obtained polymer was almost the same as the monomer composition added. The measurement method was the same as that in Example 17, and the performance was summarized in Table 9.
[0116] JPEG2025509434000025.jpg123164
[0117] Examples 25-29 The process adopted in Examples 25-29 was the same as that in Example 17, except that the synthesis experiments were carried out using monomer I with a different structure. The polymer solution was measured using a gas chromatograph mass spectrometer, and the residual mass concentration of each monomer was less than 0.1%, of which the residual concentration of HEMA was less than 0.05%, indicating that the monomer composition of the obtained polymer was almost identical to the monomer composition added. The structure of Monomer I in Example 25 is CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)3 (molecular weight 500), and is represented as Si-5Me. The structure of Monomer I in Example 26 is CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C8H 17 (molecular weight 500) and is designated as Si-5Oct. The structure of Monomer I of Example 27 is CH2=C(CH3)C(O)-(NH)-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 (molecular weight 500), and is represented as Si-5Bu(N). The structure of Monomer I of Example 28 is CH2=C(CH3)C(O)-O-(CH2)3Si(CH3)[(Si(CH3)2O]n-Si(CH3)2C4H9]2 (molecular weight 500), and is represented as Si-5-2Bu. The structure of Monomer I of Example 29 is CH2=C(CH3)C(O)-O-(CH2)3Si(CH3)[(Si(CH3)2O]n-Si(CH3)2(CH2)3OCH3]2 (molecular weight 500), and is represented as Si-5-2OMe. The measurement method was the same as in Example 17, and the performance is summarized in Table 10.
[0118] JPEG2025509434000026.jpg145164
[0119] Examples 30-33 Examples 30-33 are the same as Example 17, except that instead of HEMA, different functional monomers were added: vinylpyrrolidone (NVP), 2-isocyanatoethyl acrylate 2-butanone oxime adduct (ANCO), methacrylic acid (MAA), and glycidyl methacrylate (AGE). The polymer solutions were measured using a gas chromatograph mass spectrometer, and the residual mass concentrations of each monomer were all less than 0.1%, of which the residual mass concentrations of NVP, ANCO, MAA, and AGE monomers were all less than 0.05%, indicating that the monomer composition of the obtained polymer was almost identical to the monomer composition added. The measurement method was the same as in Example 17, and the performance is summarized in Table 11.
[0120] JPEG2025509434000027.jpg144166
[0121] Example 34 Into a 500-mL four-neck flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer, add 77 g of CH2=C(CH3)C(O)-O-(CH2)3[Si(CH3)2O]n-Si(CH3)2C4H9 (molecular weight 500) (referred to as Si-5), 15 g of N-[3-(dimethylamino)propyl]-2-methyl-2-acrylamide CH2=C(CH3)C(O)-NH-CH2CH2CH2N(CH3)2 (referred to as DN), 15 g of hydroxyethyl 8 g of ethyl methacrylate CH2=C(CH3)-C(O)-O-CH2CH2OH (referred to as HEMA) and 100 g of methyl ethyl ketone (referred to as MEK) were charged, nitrogen gas was passed for 30 minutes, the temperature was gradually raised to 50-60°C, 1.4 g of tert-butyl peroxypivalate, a peroxide initiator, was charged in portions, the reaction temperature was controlled at 60°C, and the reaction was carried out for 20 hours, obtaining about 200 g of polymer A solution, with a solid content of about 50%. When the polymer solution was measured using a gas chromatograph mass spectrometer, the residual mass concentration of each monomer was less than 0.1%, of which the residual concentration of HEMA was less than 0.05%, indicating that the monomer composition of the obtained polymer was almost the same as the monomer composition added. 295 g of water and 5.8 g of glacial acetic acid were added, and the mixture was stirred while keeping at 70° C. for 1 hour or more, and MEK in the polymer A solution was distilled off under reduced pressure to obtain an aqueous dispersion with a solid content of 25%.
[0122] Examples 35-38 Examples 35-38 are the same as Example 34, except that instead of HEMA, different functional monomers were added: vinylpyrrolidone (NVP), 2-isocyanatoethyl acrylate 2-butanone oxime adduct (ANCO), methacrylic acid (MAA), and glycidyl methacrylate (AGE). The polymer solutions were measured using a gas chromatograph mass spectrometer, and the residual mass concentrations of each monomer were all less than 0.1%, of which the residual mass concentrations of NVP, ANCO, MAA, and AGE monomers were all less than 0.05%, indicating that the monomer composition of the obtained polymer was almost identical to the monomer composition added. Measurements were performed on several articles using the aqueous dispersions synthesized in Examples 14 and 34-38 as treatment agents: 1) Fabric measurements: 100% polyester fabric and 100% cotton fabric were selected, and the treatment agent was diluted to 3% and 2.4% liquid, respectively, and immersion rolling treatment was performed, and water resistance, spray test and oil resistance were measured, respectively. 2) Paper measurement: Select two types of paper, one is 230g / m 2 The card paper was coated with a surface coating agent at a concentration of 5% and 4%, respectively. The other was 50 g / m 2 The thin papers were treated by surface sizing, and the concentrations of the treatment agents were 5% and 4%, respectively. The TAPPI oil resistance level and Cobb water absorption value were measured. 3) Measurement of paper tableware: A pulp solution with a concentration of 1% was prepared, and 2% AKD type sizing agent and 10% and 8% treatment agents were added, and the dish was made into a 10-inch dish with a weight of 20g. It was measured for 20 minutes in salad oil at 80°C, and ranked and scored according to the penetration state. It was measured for 30 minutes in hot water at 100°C, and recorded as pass or water leakage. 4) Sandstone measurement: The treatment agent of the present invention was diluted with water to a 3% and 2.4% liquid, and a sandstone sample was taken and immersed in the liquid. After taking it out, it was naturally dried for 48 hours and the temperature was increased to 25°C or higher. After that, salad oil, mustard jam, and coffee were dropped onto the surface of the sandstone, and the wet state was observed, ranked, and scored. The performance is summarized in Table 12.
[0123] JPEG2025509434000028.jpg230157
[0124] Although the present invention has been described above in terms of preferred embodiments, the present invention is not limited to these disclosed embodiments. On the contrary, those skilled in the art will recognize that several modifications and variations can be made to the described embodiments without departing from the spirit and scope of the present invention as set forth in the appended claims.
Claims
1. A copolymer comprising a repeating unit derived from a monomer I and a repeating unit derived from a monomer II, a) The general formula of the structure of monomer I is: Here, X is selected from groups represented by X-1 and X-2, R 1 and R 2 is a hydrogen atom or C 1- C 20 and n is an integer from 1 to 20; Z is selected from the structures shown below: In Z, R 3 are each independently 1 -C 20 Alkyl groups of C 6 -C 20 an aryl group of C 1 -C 20 Alkoxy group or R 4 -O-R 5 - group, and R 4 is C 1 -C 10 R is an alkyl group of the formula 5 is C 1 -C 10 wherein a is an alkylene group represented by the formula: Y 1 and Y 2 are each independently 1 -C 20 or C 6 -C 20 or having the structure R 7 are each independently 1 -C 20 or C 6 -C 20 R is an aryl group of the formula 8 are each independently 1 -C 20 Alkyl groups of C 6 -C 20 an aryl group of C 1 -C 20 Alkoxy group or R 9 -O-R 10 - group, where R 9 is C 1 -C 10 R is an alkyl group of the formula 10 is C 1 -C 10 where b is an alkylene group represented by the formula: b) The general formula of the structure of Monomer II is: Here, P is selected from groups represented by P-1 and P-2, Here, R 1 and R 2 is a hydrogen atom or C 1 -C 20 n is an integer from 1 to 20; R 3 and R 4 are each independently C 1 -C 8 or a benzyl group, 3 and R 4 is bonded to the nitrogen atom to form a morpholino, piperidino, or pyrrolidino group.
2. The mass content of repeat units from monomer I in the copolymer is 30-90%, preferably 40-85%, more preferably 50-80%, and / or The mass content of repeat units from monomer II in the copolymer is 10-70%, preferably 10-40%, more preferably 15-35%, and / or 2. The copolymer according to claim 1, wherein the repeating units according to monomer II are in the form of an ammonium salt or a nitrogen oxide.
3. R 1 and R 2 is selected from a hydrogen atom or a methyl group, In Z, R 3 are each independently 1 -C 10 Alkyl groups of C 6 -C 10 an aryl group of C 1 -C 10 or an alkoxy group of R 4 -O-R 5 - group, and R 4 is C 1 -C 10 is an alkyl group of 、 R 5 is C 1 -C 10 where 1≦a≦100, and R 7 are each independently 1 -C 10 or C 6 -C 10 R is an aryl group of the formula 8 are each independently 1 -C 10 Alkyl groups of C 6 -C 10 an aryl group of C 1 -C 10 or an alkoxy group of R 9 -O-R 10 - group, where R 9 is C 1 -C 10 is an alkyl group of 、 R 10 is C 1 -C 10 where b is an alkylene group represented by the formula: In Monomer II, R 3 and R 4 are each independently 1 -C 3 or R 3 and R 4 The copolymer according to claim 1 or 2, characterized in that: is bonded to the nitrogen atom to form a morpholino group, a piperidino group or a pyrrolidino group.
4. Z is selected from the following structures: The copolymer according to any one of claims 1 to 3, wherein Me represents a methyl group, ph represents a phenyl group, 1≦m+1≦200, preferably 1≦m+1≦100, 0≦p≦200, preferably 0≦p≦100, 0≦q≦200, preferably 0≦q≦100, and 1≦x≦10.
5. The copolymer according to any one of claims 1 to 4, characterized in that the monomer II is one or more selected from the group consisting of dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminoethyl (meth)acrylate, diethylaminopropyl (meth)acrylate, dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, dipropylaminoethyl (meth)acrylamide, dimethylaminopropyl (meth)acrylamide, diethylaminopropyl (meth)acrylamide, and dipropylaminopropyl (meth)acrylamide.
6. The copolymer further comprises a repeat unit of at least one other monomer selected from monomer III, monomer IV, and monomer V; The general formula for the structure of Monomer III is: Here, G is selected from groups represented by G-1 and G-2, In the formula, R 1 represents a hydrogen atom or a methyl group, R 2 is C 2 -C 4 and may contain alkylene groups having different carbon numbers in one molecule; q is an integer of 1 to 50; R 3 is a hydrogen atom or C 1 -C 20 R represents an alkyl group of the formula 4 represents a hydrogen atom or a methyl group, and n is an integer of 0 to 10. Monomer IV is a monomer having an anionic group and a polymerizable unsaturated group, the anionic group being a carboxyl group or a sulfonic acid group; The copolymer according to any one of claims 1 to 5, wherein the monomer V is selected from a monomer containing a pyrrolidone structure and a polymerizable unsaturated group, a monomer having a blocked isocyanate group and a polymerizable unsaturated group, a monomer having an alkoxysilyl group and a polymerizable unsaturated group, or a monomer having a glycidyl group and a polymerizable unsaturated group.
7. The copolymer according to claim 6, characterized in that the mass content of repeating units from monomer I in the copolymer is 30-90%, preferably 40-85%, more preferably 50-80%, the mass content of repeating units from monomer II in the copolymer is 5-65%, preferably 10-40%, more preferably 15-35%, and the mass content of repeating units from other monomers in the copolymer is 1-30%.
8. Monomer III is one or more selected from 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and methoxypolyethylene glycol (meth)acrylate; Monomer IV is selected from (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, vinylsulfonic acid, (meth)allylsulfonic acid, styrenesulfonic acid, vinylbenzenesulfonic acid, acrylamido tert-butylsulfonic acid, or salts thereof; Monomer V is selected from a monomer containing a pyrrolidone structure and a polymerizable unsaturated group, a monomer having a blocked isocyanate group and a polymerizable unsaturated group, a monomer having an alkoxysilyl group and a polymerizable unsaturated group, or a monomer having a glycidyl group and a polymerizable unsaturated group; 8. The copolymer according to claim 6 or 7, characterized in that the mass content of repeat units from monomers III, IV and V is 1-30%.
9. A treatment agent comprising the copolymer according to any one of claims 1 to 8 and a solvent, wherein the solvent comprises water and / or an organic solvent, Preferably, the organic solvent is one or more of acetone, methyl ethyl ketone, 4-methyl-2-pentanone, ethyl acetate, butyl acetate, N-methyl-2-pyrrolidone, N,N-dimethylformamide, ethanol, isopropanol, n-propanol, butyl carbitol, dipropylene glycol monomethyl ether.
10. (1) polymerizing a monomer in an organic solvent to obtain a copolymer solution; (2) optionally, dispersing the copolymer solution in water and then removing the organic solvent, or removing the solvent and then dispersing the copolymer solution in water; (3) optionally, adding an acid to the copolymer solution to convert amino groups in the copolymer into ammonium salts; 10. The method for producing the treating agent according to claim 9, further comprising the step of: (4) optionally treating the copolymer solution with an aqueous hydrogen peroxide solution to convert the amino groups to oxynitrides.
11. A treatment method comprising treating an article to be treated with the copolymer according to any one of claims 1 to 8, the treatment agent according to claim 9, or the treatment agent produced by the method according to claim 10, and preferably the treatment comprises a surface coating or immersion treatment.
12. 11. Application of the copolymer according to any one of claims 1 to 8, the treating agent according to claim 9, or the treating agent produced by the method according to claim 10 in a surface coating or immersion treatment process for textile fabrics, leather, nonwoven fabrics, asbestos, fur, concrete, natural stone, paper, or plastic.
13. Application of the copolymer according to any one of claims 1 to 8 or the treatment according to claim 9 or the treatment produced by the method according to claim 10 in paper products, preferably said application being in surface coating, surface sizing or wet part addition of paper, paperboard and pulp moulds.
14. A product treated with the copolymer according to any one of claims 1 to 8, the treatment agent according to claim 9, or the treatment agent produced by the method according to claim 10, wherein the product is a textile fabric, leather, nonwoven fabric, asbestos, fur, concrete, natural stone, paper, or plastic.
15. A paper product comprising paper and, adhered to the paper (inside and / or surface), the copolymer according to any one of claims 1 to 8, the treating agent according to claim 9, or the treating agent produced by the method according to claim 10.
Citation Information
Patent Citations
Polymer for cosmetic for hair
JP1991128909A
Actinic energy ray-curable aqueous emulsion composition
JP2002173516A
Water repellent agent
JP2003034784A
Cited By
Silicone acrylate copolymer, paper coating composition containing the same, pulp slurry, and paper made therefrom
KR102990644B1